Pengaruh Komunikasi Dan Standar Operasional Prosedur Terhadap Produktivitas Karyawan PT Idefab Cipta Jakarta Barat - Rizki Wahyu Aditiya; Henni Marlinah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
. This study aims to determine the effect of communication and standard operating procedures on employee productivity partially and simultaneously at PT Idefab Cipta West Jakarta. This type of research uses quantitative methods, a population of 120 employees and a sampling technique using the Slovin formula, namely 55 respondents. Data analysis techniques use: data instrument test, classical assumption test, simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination. Hypothesis testing uses the t test and F test. Based on the test results, a positive value of t count> t table or (11.368> 2.006) is obtained. This is also strengthened by a significance value of 0.000 <0.05. Thus, Ho is rejected with H1 accepted, this indicates that there is a significant influence between Communication on Employee Productivity. Based on the test results, a positive value of t count> t table or (5.064> 2.006) is obtained. This is also strengthened by a significance value of 0.000 <0.05. Thus, Ho is rejected and H1 is accepted, indicating a significant effect between standard operating procedures and employee productivity. Based on the ANOVA analysis, the calculated F value was 314.004, while the F table (α 0.05) for n = 52 was 3,18. Therefore, the calculated F value is greater than the F table (α 0.05), or 314.004 > 3,18, with a significance level of 0.000 (0.000 < 0.05). Therefore, it can be concluded that communication (X1), standard operating procedures (X2), and employee productivity jointly influence employee productivity (Y).